Characterizing sustainability aesthetics of buildings and environments: methodological frame and pilot application to the hybrid environments - Daugelaite, Aurelija; Dogan, Huriye Armagan; Grazuleviciute-Vileniske, Indre (Landscape Architecture and Art, 2021)
Growing environmental awareness and emerging design and performance requirements related with the implementation of sustainability goals inevitably have an influence on construction, architecture, urban design and the development of our built environment in general. This influence is reflected both in the increasingly efficient ecological performance of built structures and the growing array of related technologies, and in the aesthetic expression of these environmentally conscious designs. The aesthetic expression of sustainability concept and values is sometimes referred to as sustainability aesthetics. The aim of this research is to develop and test a methodological framework for characterizing the sustainability aesthetics of the built environments. The elaborated methodological framework integrates biophilic design, sustainability aesthetics, regenerative design and genius loci as the most promising approaches, allowing the integration of human and environmental concerns. To test the framework, we selected historic built environments that reflect long-lasting sustainable co-existence between humans and their environment and represent hybrid characteristics of both architectural and urban space. One of the purposes selecting these environments for the case study was to determine the features of an organically evolved sustainability aesthetics that could become a valuable source of inspiration for architectural design and management of the built environments.